1984
DOI: 10.1177/027836498400300405
|View full text |Cite
|
Sign up to set email alerts
|

On the Complexity of Motion Planning for Multiple Independent Objects; PSPACE- Hardness of the "Warehouseman's Problem"

Abstract: Coordinated motion planning for a large number af three-di mensional objects in the presence of obstacles is a computa tional problem whose complexity is important to calibrate. In this paper we show that even the restricted two-dimensional problem for arbitrarily many rectangles in a rectangular region is PSPACE-hard. This result should be viewed as a guide to the difficulty, of the general problem and should lead researchers to consider more tractable restricted classes of motion problems of practical intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
203
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(204 citation statements)
references
References 3 publications
0
203
0
1
Order By: Relevance
“…This approach usually comes with stronger theoretical guarantees such as completeness [29,39,40,41,44] or even optimality [51] of the returned solutions. However, due to the computational hardness of MRMP [21,22,26,42,45], coupled techniques do not scale well with the increase in the number of robots. We do mention that, when simplifying assumptions are made concerning the separation of initial and goal positions, MRMP can be solved in polynomial time, as function of the number of robots and the complexity of the workspace environment (see, [1,43,47]).…”
Section: A Multi-robot Motion-planningmentioning
confidence: 99%
“…This approach usually comes with stronger theoretical guarantees such as completeness [29,39,40,41,44] or even optimality [51] of the returned solutions. However, due to the computational hardness of MRMP [21,22,26,42,45], coupled techniques do not scale well with the increase in the number of robots. We do mention that, when simplifying assumptions are made concerning the separation of initial and goal positions, MRMP can be solved in polynomial time, as function of the number of robots and the complexity of the workspace environment (see, [1,43,47]).…”
Section: A Multi-robot Motion-planningmentioning
confidence: 99%
“…Sliding-block puzzles generalize the 15-puzzle by allowing unmovable blocks, and blocks that are larger than 1 × 1. Generally the goal of a sliding-block puzzle is to move a block to a single location (the "warehouseman's problem" [21]), to find out if a single block is movable [18,19], or somehow reorder all blocks [20]. In contrast, in the kissing problem, the objective is for all blocks to touch each other.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in general, sliding-block puzzles are PSPACE-complete [25,26]. However, under certain simplifying assumptions and for cases of such puzzles like the one we consider here (Figure 2), a polynomial algorithm can be constructed to move a single block from any initial position to any final position [26].…”
Section: A Case Study: the Sliding Block Puzzlementioning
confidence: 99%